An update on clinical significance of use of THSD7A in diagnosing idiopathic membranous nephropathy: a systematic review and meta-analysis of THSD7A in IMN. (15th October 2018) - Ren, Song; Wu, Changwei; Zhang, Yuan; Wang, Amanda Y.; Li, Guisen; Wang, Li; Hong, Daqing
Abstract: Background : THSD7A is a new target antigen of idiopathic membranous nephropathy (IMN). Moreover, malignancies are also found in patients with THSD7A-positive membranous nephropathy. We aimed to systematically evaluate the prevalence of THSD7A in IMN patients and malignancies in THSD7A-positive patients. Methods : We searched English and Chinese database to 31 December 2017 with the term 'THSD7A' or 'thrombospondin type 1 domain-containing 7A'. Meta-analysis was used to explore the positive rate of THSD7A in the IMN patients. Subgroup analysis was performed according to the race, sample size, and detecting method of THSD7A. Results : Ten studies involving 4121 participants were eventually included. The prevalence of THSD7A was 3% (95% CI, 3%–4%) in all patients and 10% (95% CI, 6%–15%) in PLA2R-negative patients. 77 patients had positive circulating antibodies, and the prevalence of THSD7A was also low at 3% (95% CI, 2%–4%). Overall, 72 patients had positive THSD7A staining on renal biopsy, and the prevalence was 3% (95% CI 2%–4%). Subgroup analysis showed significant differences in the prevalence of THSD7A based on the study sample sizes, however, no significant differences were seen in different ethnic groups. Furthermore, among THSD7A-positive patients, 3/10 studies reported malignancies with the incidence varied from 6% to 25%. Conclusions : The prevalence of THSD7A is more common in the PLA2R-negative patients than the IMN patients. Screening for malignancies in THSD7A-positive MN patients is recommended.